Im Transformation of Accounting Teacher Competencies in Vocational High Schools: Real-Case-Based EMKM SAK Training at MGMP Tangerang City - Setiyawati, Hari; Mappanyukki, Ratna; Arwati, I Gusti Ayu; Zulkafi, Abdul Hadi; Indiyani, Indiyani; Indirwanti, Ena Rolika (Jurnal Pengabdian kepada Masyarakat Nusantara, 2026)
Vocational high school accounting teachers who are members of the Tangerang City Accounting MGMP (64 vocational high schools) face a competency gap in understanding and implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), particularly in preparing financial reports based on real cases. This condition has a direct impact on students’ low readiness to face the demands of business and industrial competencies. As a solution, this Community Service (PkM) activity offers practice-based training and mentoring that includes strengthening the conceptual understanding of SAK EMKM as well as technical practice in preparing financial position statements, income statements, and notes to the financial statements using real MSME cases. The activity was carried out in three stages, namely: pre-test and material presentation, guided practice in preparing financial reports, and post-test and reflection. The results of the activity showed an average increase in participants’ conceptual understanding scores of 35% and technical skills in preparing financial reports by 40% based on the pre-test and post-test results. This activity contributes significantly to strengthening the pedagogical capacity of vocational accounting teachers and improving the quality of accounting learning based on the latest standards in Tangerang City vocational high schools on an ongoing basis